Aggregation‐Induced‐Emission‐Active Macrocycle Exhibiting Analogous Triply and Singly Twisted Möbius Topologies. Issue 33 (14th July 2015) - Wang, Erjing; He, Zikai; Zhao, Engui; Meng, Luming; Schütt, Christian; Lam, Jacky W. Y.; Sung, Herman H. Y.; Williams, Ian D.; Huang, Xuhui; Herges, Rainer; Tang, Ben Zhong
Abstract Molecules with Möbius topology have drawn increasing attention from scientists in a variety of fields, such as organic chemistry, inorganic chemistry, and material science. However, synthetic difficulties and the lack of functionality impede their fundamental understanding and practical applications. Here, we report the facile synthesis of an aggregation‐induced‐emission (AIE)‐active macrocycle (TPE‐ET) and investigate its analogous triply and singly twisted Möbius topologies. Because of the twisted and flexible nature of the tetraphenylethene units, the macrocycle adjusts its conformations so as to accommodate different guest molecules in its crystals. Moreover, theoretical studies including topological and electronic calculations reveal the energetically favorable interconversion process between triply and singly twisted topologies.